“When you go out while nobody is going anymore”: A Belated Story of Beginning - Israeli, Tami (MiKAN, 2016)
For reasons yet to be explored there is no scholarly narrative of the departure point for Hedva Harechavi’s poetry. The following essay wishes to seek out the connections between the academic haze surrounding Harechavi’s beginning and the mode through which this beginning takes place. As we shall see, Harechavi’s point of departure subverts the very concept of beginning. Herachavi twists and sabotages most of the features and pre-conditions of the lyric mode, especially with regard to the establishing of the poetic voice. Thus, this body of work problematizes the Oedipal structure and challenges the very mode of dynastic inheritance.